Research of probability of a choice by the passenger of a type of transport on competitive transport market (Transport systems and technologies, 2019)
The article deals with the problems that exist in the passenger suburban complex and affect the passenger‟s choice of the type of transport on the competitive transport market. To improve the competitiveness of rail passenger traffic, factors that directly affect the competitive struggle in the market of transport services are analyzed. A mathematical model is proposed that enables to make practical calculations of the probability of a passenger choice of the mode of transport (on the example of the choice of alternative competing carriers) in the transport market. This model makes it possible to assess the chances of rail transport for the carriage on this market, depending on the technological, organizational and other factors of transportation. Proposed analytical dependencies and calculation formulas make it possible to make practical calculations of the probability of potential passenger selecting a particular type of transport (for example, railway and road transport). On the basis of the conducted researches it is possible to carry out integrated, systematically related calculations of important technological and organizational parameters of suburban passenger transportation. It has been established that the significant effect on increasing the volume of passenger transportation by rail in conditions of its competition with the automobile improves the organization of transportation of passengers, first of all, by shortening the waiting time of the trip and increasing the route speeds.
Keywords: passenger, railway transport, road transport, competitive transport market, suburban connections, probability of choice